1986
DOI: 10.1121/1.2023837
|View full text |Cite
|
Sign up to set email alerts
|

Creak as a sociophonetic marker

Abstract: Previous investigations into creak (vocal fry or pulse phonation) concentrated on two aspects: establishment of the physiological, acoustic, or perceptual nature of creak compared with other phonations; or separation of its characteristics in normal speech from pathological voices. The approach here is entirely different. Taking the phonetic and linguistic incidence of creak in normal speech in two accents of English as a starting point, quantitative description of its occurrence is provided. Data are taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 0 publications
1
46
1
Order By: Relevance
“…A comparison of these data with Coadou (2007) suggests that NWY speakers of both sexes and in all age brackets tend to use creaky voice more markedly and to a greater extent than speakers using other accents of English. This tallies with the findings of Coadou (2007 : 184-196) and Henton & Bladon (1988), who have shown that northern speakers of English English tend to use creaky voice more extensively than Southerners. Creak and creaky voice are normally associated with a low register (50 to 100 Hz for 'pure' creak), and it is not without interest to note that, when mimicking Southerners, Yorkshire speakers usually use higher voice pitch than in normal speech situations (Daniels, personal communication).…”
Section: -Phonatory Settingssupporting
confidence: 72%
“…A comparison of these data with Coadou (2007) suggests that NWY speakers of both sexes and in all age brackets tend to use creaky voice more markedly and to a greater extent than speakers using other accents of English. This tallies with the findings of Coadou (2007 : 184-196) and Henton & Bladon (1988), who have shown that northern speakers of English English tend to use creaky voice more extensively than Southerners. Creak and creaky voice are normally associated with a low register (50 to 100 Hz for 'pure' creak), and it is not without interest to note that, when mimicking Southerners, Yorkshire speakers usually use higher voice pitch than in normal speech situations (Daniels, personal communication).…”
Section: -Phonatory Settingssupporting
confidence: 72%
“…This finding, previously been reported by Henton and Bladon (1988), may relate to declination, whereby fundamental frequency gradually diminishes over the course of an utterance. Creaky voice appears at the ends of utterances when favorable aerodynamic conditions for modal voicing have faded.…”
Section: Linguistic Factorsmentioning
confidence: 61%
“…2) c. distributional constraints on morphemes, stems, words, ultimately templatic, e.g. the maximum CVCVCV "prosodic stem" in Tiene, where C 2 must be coronal and C 3 must be labial or velar (Ellington 1977, Hyman 2006 d. demarcation: initiality-/finality-effects (Keating et al 2003, Barnes 2006, final glottalization (Henton & Bladon 1988, Hyman 1988; also root-affix asymmetries, stem-initial prominence (Beckman 1997, Smith 2002 e. intonation based on the "grammaticalization" of three biological codes (Gussenhoven 2004, ch. 5) f. "boundary narrowing": pause > phrase > word; phonologization of prepausal effects, which can include final devoicing, debuccalization, glottalization, lengthening, "nasal pause" (Aikhenvald 1996:511-512), and loss I would like to suggest that the "pronunciation in isolation" form of a word is its lexical representation.…”
Section: Other Types Of Phonologizationmentioning
confidence: 99%
“…The phonologization of prepausal effects is perhaps less clear. It is tempting to interpret languages which insert prepausal glottal stops as having phonologized utterance-final creakiness, as in British English (Henton & Bladon 1988):…”
Section: Other Types Of Phonologizationmentioning
confidence: 99%